Efektifitas Desain Lembar Kerja Mahasiswa Terintegrasi Internet untuk Mengembangkan Kemampuan Penalaran Matematis Mahasiswa - Selvi Riwayati; Yuriska Destania (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
The adequate learning resources as support for student learning activities was one of the factors supporting the learning process successful. The use of textbooks as a source of learning did not support thinking activities, especially students' mathematical reasoning abilities. The textbooks so far only emphasize the understanding of the concept while the students' mathematical reasoning abilities were less noticed. This research intends to develop student worksheets that are valid, practical and effective in developing mathematical reasoning abilities and can be accessed via the internet. The research model used is Research and Development (R & D). To see the effectiveness of the product carried out an experiment. The results showed that through the learning assisted students worksheets that integrated the internet, the average of students' mathematical reasoning abilities were increased.